1969
DOI: 10.1001/archinte.1969.00300130019004
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Insulins

Abstract: Plasma insulin has been characterized by its biologic, immunologic, physical, and chemical similarity to pancreatic insulin. A higher molecular weight heterogenous component (peak "b") of pancreatic insulin that contains the biosynthetic precursor of insulin (proinsulin) has recently been described. Plasma insulin as measured by radioimmunoassay is composed of at least two components. Filtration of plasma on G-50 Sephadex yields a major component ("little" insulin) which is indistinguishable from the major com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

1969
1969
1985
1985

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 16 publications
4
11
0
Order By: Relevance
“…Insulin precursors also were secreted into the media, an observation which is compatible with those of other investigators, where proinsulin was found in plasma, urine and incubation media of isolated islets (25)(26)(27). However, how and why these precursors are secreted, as well as what role they play in normal and diabetic individuals, remains an intriguing question.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Insulin precursors also were secreted into the media, an observation which is compatible with those of other investigators, where proinsulin was found in plasma, urine and incubation media of isolated islets (25)(26)(27). However, how and why these precursors are secreted, as well as what role they play in normal and diabetic individuals, remains an intriguing question.…”
Section: Discussionsupporting
confidence: 87%
“…The relationships of proinsulin and intermediate in the media are not clear. However, their presence in the media is compatible with the observance of circulating big insulin which increases relative to insulin during the later phases of a glucose tolerance test (25). Proinsulin also has been found in human serum and urine and in the incubation media of isolated islets (26,27).…”
Section: Resultsmentioning
confidence: 64%
“…It is, of course, possible that the secretory mechanism is intact and the failure lies in the inability of the islet cell to convert a proinsulin to an active hormone. 19 ' 20 At this stage of beta cell failure, insulin secretion is normal during the fasting state. The fact that abnormally high secretion after a stimulus is insufficient for homeostasis was shown by the lower than normal insulin/glucose ratios.…”
Section: Discussionmentioning
confidence: 99%
“…15 The demonstration that immunoreactive insulin in plasma is eluted from Sephadex G-50 gel in a region corresponding to porcine proinsulin 3 has led to the speculation that proinsulin "may account for the high but seemingly ineffective levels of immunoreactive in- sulin which are often noted in the early stages of diabetes and in other diseases with so-called insulin resistance." 4 In a more recent publication Gorden and Roth 16 have concluded that "big insulin" in plasma does not account for the hyperinsulinism observed in thin diabetics, acromegalics, or patients with myotonic dystrophy, but have left open the question of whether big insulin may partially account for the hyperinsulinemia observed in some patients with obesity and normal subjects with starvation diabetes.…”
Section: Discussionmentioning
confidence: 99%